2021
DOI: 10.3389/fnut.2021.623698
|View full text |Cite
|
Sign up to set email alerts
|

Red Clover Isoflavones Influence Estradiol Concentration, Exercise Performance, and Gut Microbiota in Female Mice

Abstract: In red clover (Trifolium pratense L.; RC) the main compound is isoflavones, which are selective estrogen receptor modulators for maintaining female health. Isoflavones exert antifatigue effects during exercise in high-temperature environments. This study aimed to investigate the effect of RC supplementation on gut microbiota composition to determine whether it improves intestinal barrier function and exercise performance. Female ICR mice were divided into four groups (n = 8 per group) and orally administered R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 50 publications
(57 reference statements)
3
7
0
6
Order By: Relevance
“…A recent study reported an increase in the relative abundance of Pseudobutyribrio alongside increases in circulating estradiol and progesterone in female mice following red clover supplementation. ( Chen et al, 2021 ) This is consistent with the %RA of Pseudobutyrivibro being greater in adolescents taking OCP. To our knowledge, data on steroidogenic regulation of Pseudobutyrivibro are lacking in humans.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study reported an increase in the relative abundance of Pseudobutyribrio alongside increases in circulating estradiol and progesterone in female mice following red clover supplementation. ( Chen et al, 2021 ) This is consistent with the %RA of Pseudobutyrivibro being greater in adolescents taking OCP. To our knowledge, data on steroidogenic regulation of Pseudobutyrivibro are lacking in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Os constituintes principais de T. pratense (trevo vermelho) são as isoflavonas que são moduladores seletivos de receptores de estrogênio. Isto significa que as isoflavonas podem agir como agonistas ou antagonistas dos receptores estrogênicos (Chen et al, 2021). Os autores empregaram, ainda neste estudo, o produto com black cohosh que se trata da espécie Cimicifuga racemosa (L.) Nutt., pertencente à família Ranuculaceae, nativa da metade oriental dos Estados Unidos e Canadá.…”
Section: Discussionunclassified
“…O S-equol é produzido pela ação do microbioma intestinal das mulheres e estudos demonstram que 50% das asiáticas e somente 20% das mulheres ocidentais caucasianas apresentam na flora do intestino, bactérias que transformam a daidzeina em S-equol. Essa transformação encontra-se demonstrada na Figura 2 (Chen;Ko;Chen, 2019). Utain e col (2015) realizaram um estudo de revisão sobre o potencial do S-equol para o alívio de sintomas no período menopausa.…”
Section: Discussionunclassified
“…Mice showed a significant decrease in total body fat mass and an increase in exhaustive swimming time, grip strength, and muscle glycogen (Chen et al, 2021).…”
Section: Ethnopharmacological and Traditional Uses Of T Pratensementioning
confidence: 96%
“…These findings were strongly supported by evaluating the efficacy of feeding female ICR mice with red clover isoflavones supplementation for 6 weeks. Mice showed a significant decrease in total body fat mass and an increase in exhaustive swimming time, grip strength, and muscle glycogen (Chen et al, 2021).…”
Section: Red Clover (T Pratense)mentioning
confidence: 99%